Інсиденталоми надниркових залоз: проблеми діагностики - Kvachenyuk, A.N.; Lucenko, L.A.; Galuzinskaya, O.I. (Ендокринологія | Endokrynologia, 2011)
Інсиденталоми надниркових залоз: проблеми діагностики